An introduction to cyber peacekeeping. (15th July 2018) - Robinson, Michael; Jones, Kevin; Janicke, Helge; Maglaras, Leandros
Abstract: Cyber is the newest domain of war, and the topic of cyber warfare is one that is receiving increasing attention. Research efforts into cyber warfare are extensive, covering a range of issues such as legality, cyber weapons and deterrence. Despite all of the research activity around cyber warfare, one aspect has been largely overlooked: the restoration of peace and security in its aftermath. In this article, we present the argument that cyber warfare will threaten civilian peace and security long after a conflict has ended, and that existing peace operations will be required to evolve in order to address this threat. We explore how existing UN peacekeeping operations could be adapted, in ways that would be both feasible and valuable towards maintaining and restoring peace in a region. We conclude that the path to cyber peacekeeping will not be easy, but that it is an evolution that must begin today so that we can be prepared for the conflicts of the future.